Giant non-functioning adrenocortical carcinoma: an unusual tumour presentation - Potnis, Abhishek R.; Boralkar, Ajay K.; Rafe, Abdul; Jadhav, Sarojini P. (International Surgery Journal, 2020)
Adrenocortical carcinoma is a rare tumour with incidence of 1 per million all over the world. Age distribution is bimodal with peaks occurring at 5-20 years and 40-50 years. Tumours greater than 9 cm commonly involve inferior vena cava (IVC) or right side of heart. 80 percent of the carcinomas are functional. We describe a case report of a rare tumour of a non-functioning adrenocortical carcinoma in a 40 year old female having incidence of 0.5/million world over with no extra-adrenal spread at presentation without IVC or right heart involvement in spite of having a large size of 12 cm. Patient underwent successful surgical extirpation with adjuvant radiotherapy with regular follow ups and disease free survival since the surgery. It is imperative to determine hormone levels in symptomatic and asymptomatic patients with adrenal masses. The possibility of adrenocortical carcinoma should not be ruled out in a functioning/non-functioning tumour. All solid incidentalomas on computed tomography (CT)/magnetic resonance imaging (MRI) greater than 5 cm in size should be removed surgically with adjuvant therapy consideration after histopathological reporting.